Research progress on the impact of intratumoral microbiota on the immune microenvironment of malignant tumors and its role in immunotherapy - Xu, Jiamei; Cheng, Min; Liu, Jie; Cui, Mengqi; Yin, Beibei; Liang, Jing (Frontiers in Immunology, 2024)
Microbiota has be closely related to human beings, whose role in tumor development has also been widely investigated. However, previous studies have mainly focused on the gut, oral, and/or skin microbiota. In recent years, the study of intratumoral microbiota has become a hot topic in tumor-concerning studies.Intratumoral microbiota plays an important role in the occurrence, development, and response to treatment of malignant tumors. In fact, increasing evidence has suggested that intratumoral microbiota is associated with malignant tumors in various ways, such as promoting the tumor development and affecting the efficacy of chemotherapy and immunotherapy. In this review, the impact of intratumoral microbiota on the immune microenvironment of malignant tumors has been analyzed, as well as its role in tumor immunotherapy, with the hope that it may contribute to the development of diagnostic tools and treatments for related tumors in the future.